IMPLIKASI HUKUM KETIDAKAKTIFAN KOPERASI TERHADAP PERTANGGUNGJAWABAN PENGURUS: STUDI PADA DINAS PERDAGANGAN DAN KOPERASI UKM KABUPATEN LABUHANBATU UTARA - Rizki , Sauki; Sukarja, Detania; Robert, Robert (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The inactivity of cooperatives constitutes a significant legal issue, particularly in relation to the accountability of cooperative management. Although an inactive cooperative no longer conducts business activities, it legally remains a corporate entity as long as its dissolution has not been formally executed in accordance with statutory provisions. This condition creates legal uncertainty, as cooperatives are expected to continuously perform their economic and social functions. This study aims to analyze the legal implications of cooperative inactivity on the liability of cooperative managers and to examine the role of the Department of Trade and Cooperatives for Micro, Small, and Medium Enterprises (MSMEs) in Labuhanbatu Utara Regency in supervising and fostering inactive cooperatives. The research employs a normative juridical method supported by empirical data, obtained through document analysis and interviews, and analyzed qualitatively. The findings indicate that the inactive status of a cooperative does not eliminate the legal and civil liability of its management. Cooperative managers remain responsible for the management and administration of the cooperative as stipulated in Articles 31 and 34 of Law Number 25 of 1992 on Cooperatives, particularly when losses arise due to negligence or intentional misconduct. Furthermore, the Department of Trade and Cooperatives for MSMEs plays a strategic role through guidance, supervision, governance assistance, capacity building for managers, and periodic monitoring and evaluation. These efforts aim to encourage cooperative revitalization or, where necessary, lawful dissolution to ensure legal certainty, protect members and third parties, and promote sustainable cooperative development.